2012
DOI: 10.1093/ehjci/jes103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cardiovascular magnetic resonance perfusion imaging: inter-study reproducibility

Abstract: AimsTo evaluate the inter-study reproducibility of quantitative cardiovascular magnetic resonance (CMR) myocardial perfusion imaging and the influence of diurnal variation on perfusion. Data on these are limited, despite being crucially important for performing serial examinations both in clinical practice and in trials. Methods and resultsSixteen healthy volunteers underwent high-resolution 3 T perfusion imaging three times during a single day to evaluate inter-study reproducibility and the effects of diurnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
(30 reference statements)
1
20
0
2
Order By: Relevance
“…While MBFs and MPR from the Fermi model have been validated by microspheres, it is still not clear if these values reflect perfusion or if extraction or permeability also needs to be considered. Even if the MBFs reported here and previously more correctly reflect a flow index, measuring their repeatability is important.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…While MBFs and MPR from the Fermi model have been validated by microspheres, it is still not clear if these values reflect perfusion or if extraction or permeability also needs to be considered. Even if the MBFs reported here and previously more correctly reflect a flow index, measuring their repeatability is important.…”
Section: Discussionmentioning
confidence: 83%
“…Table summarizes the results from previously published results on repeatability of perfusion cardiovascular MRI . The studies listed in Table all made use of ECG‐gated, breath‐held acquisitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[43][44][45][46][47] Direct comparison with the reproducibility of PET-based myocardial perfusion measurements is hampered by different measures of repeatability used in different studies and wide time ranges between the repeated measures in some studies. However, the repeatability coefficients reported in some MRI studies 44,47 are somewhat higher and the ICC somewhat lower 44,46 than in the previously mentioned PET-studies. 41,42 Morton et al 21 reported weak correlations for absolute perfusion values when comparing rest and stress perfusion values separately (r = 0.32 and r = 0.37, respectively).…”
Section: Discussionmentioning
confidence: 99%